The Influenced Factor of Revisits Patient Intention to The Executive Polyclinic Hospital - A. Stefanus Andi Pranata; Andry Andry; Rokiah Kusumapradja (Journal of Multidisciplinary Academic, 2021)
The executive polyclinic is one of the health services options available in hospitals, where the trend of visits tends to increase at this time, both prior visits and new visits. The determinants that influence the visit have not been extensively studied empirically. The purpose of this study is to look at the impact of service quality and marketing mix parameters on the frequency of patient return visits, as mediated by patient satisfaction, at Hermina Ciruas Hospital's Executive Polyclinic. This study used a cross-sectional strategy with 201 respondents who were frequent visitors to the Executive Polyclinic of Hermina Ciruas Hospital. The independent variables in this study are reliability, tangibility, responsiveness, assurance, empathy, customer needs, cost, convenience, and communication. Patient satisfaction is the intervening variable. Meanwhile, the intention to return patient is the dependent variable. Path analysis is a type of data analysis. The customer needs factor (b=0.226; p=0.006) has a direct impact on patient satisfaction with the Executive Polyclinic's services. The patient's intention to return to the Executive Polyclinic was influenced by the assurance factor (b=-0.077; p=0.009), tangibility (b=0.257; p=0.027), cost (b=0.043; p=0.042), convenience (b=0.075; p=0.002), and patient satisfaction (b=0.232; p=0.012). The most important aspect influencing the patient's decision to return to the Executive Polyclinic is tangibility. Hospitals must concentrate on maintaining and improving physical facilities in order to maintain the desire for recurrent patient visits